Agile Quality Management Framework in Construction Projects (AQMFCP) - Neamah Ahmed, Mohammed; Rasheed Mohammed, Sawsan (International Journal of Engineering and Technology, 2018)
In project management there has been a shift from traditional project management to the Agile Project Management (APM) style. The proposed Agile Quality Management Framework in Construction Projects will be built as a sequence of procedure that deals with a project from primary vision of project to the final delivery of project, will trace alignment and discover a contact between Agile and Traditional Project Management (TPM) concepts and find contact points among two of the more used Agile frameworks (scrum) and one of the more confirmed Project Management framework (PMBOK®) processes. This will result in a recognition of comparable areas between scrum and PMBOK® processes. Agile quality Management Framework is a new agile framework that covers the whole project lifecycle. The goal of the framework is to assist the project managers to adapt a more flexible approach to managing and implementing the construction project. The findings arrive that the agile project management using the Scrum methodology profits effectiveness procedures and a lower duration of process, ensuring value of quality planning and control inputs.
Keywords: Agile; Construction Project; Scrum; PMBOK; Quality.